Trends in racial and ethnic disparities in the health-related quality of life of older adults with breast cancer: a SEER-MHOS national database study - Nicki Karimi-Mostowfi; Fang-I Chu; Trudy C. Wu; Matthew J. Farrell; Wisdom Akingbemi; Ann C. Raldow (Health and Quality of Life Outcomes)
Abstract Purpose To examine racial and ethnic disparities in Health-Related Quality of Life (HRQOL) in older adults with breast cancer, both pre- and post-diagnosis. Methods Using the SEER-MHOS database, we included patients ≥ 65 years old with breast cancer who completed the Health Outcomes Survey within 24 months pre- and post-diagnosis, and who were non-Hispanic White, non-Hispanic Asian or Pacific Islander, non-Hispanic Black or African American, or Hispanic. HRQOL data was measured via the Physical and Mental Component Summary (PCS, MCS). Univariable and multivariable linear regression models were fitted to assess for potential disparities between races and ethnicities. Results On univariable regression models, a numerical drop in mean scores of PCS and MCS was found among all racial/ethnic groups between pre- and post-diagnosis. Among patients in the pre-diagnosis cohort who would be diagnosed with stage IV breast cancer, race was found to be a predictor of PCS with overall significance (p = 0.04). On the local test, compared with Black individuals, White individuals had higher pre-diagnosis PCS scores (+ 13.32, p = 0.03). Race/ethnicity was not found to be a predictor in PCS or MCS scores otherwise. Conclusion Among older patients diagnosed with stage IV breast cancer, White individuals had better physical HRQOL than Black patients’ pre-diagnosis. The decrease in the numerical HRQOL scores of the physical domain in all groups post-diagnosis highlights the potential negative physical impact of breast cancer has on patients, demonstrating the need for determining the proper resources and support to improve physical HRQOL following diagnosis.